Quality of life, fatigue, and sleep problems in pancreatic cancer patients: a randomized trial on the effects of exercise - Steindorf, Karen; Clauss, Dorothea; Tjaden, Christin; Hackert, Thilo; Herbolsheimer, Florian; Bruckner, Thomas; Schneider, Lutz; Ulrich, Cornelia; Wiskemann, Joachim (Deutsches Ärzteblatt, 2019)
Improving quality of life (QoL) is an important treatment goal in pancreatic cancer patients. Although the beneficial effects of exercise on QoL are well understood, few studies have investigated more aggressive cancers such as pancreatic cancer.
Gesehen am 20.03.2020